Manual de patologías de daños y evaluaciòn geo-referenciada de las carreteras de lastre y tierra de la red vial, correspondiente a los cantones Atahualpa, Piñas, Portovelo, Zaruma, Balsas, Marcabelì, Chilla y Las Lajas de la provincia de El Oro. - Espinoza Gallo, Johana Elizabeth (2015)
The manual pathologies aims to reduce discrepancies between inspectors when evaluating the road network in the province and support the assessment based on generally accepted criteria, thus serving inspectors any other province or municipality as a reference to assess technical way the road network Local inspected visually. Mapping surface condition will serve to estimate on a scientific basis the surface condition avoiding the use of visual inspections, this map will serve as input to a system of pavement management will be the final result of the integration of this and 9 other investigations carried out in a period of two years, as this was achieved preserve roads in good condition in order to facilitate the movement of goods and people in the province.